Judging gymnastics with biomechanics - Sands, W. M; McNeal, J. R. (Sportscience, 1999)
In sports like gymnastics, judging competitors is notoriously political and subjective. Modern biomechanics may provide an objective way to score the movement of athletes in these sports. Recently we undertook a feasibility study of such a scoring system for USA Gymnastics. Human judges often have difficulty in determining the subtle differences in trajectories and speed between competitors in compulsory vault by using video digitizing, infrared timers, and a computer algorithm. We combined the objective score with a human judge's score for form errors. The objective score successfully increased the differentiation between performances in a trial of 25 gymnasts at a competition.